Sunday

September 25, 2016
Total # Posts: 2,198

**Algebra**

x = 1.5 f ( 1.5 ) = 3 * 1.5 -2 = 4.5 - 2 = 2.5 Answer : a

*January 27, 2015*

**algebra 1**

n = even number n - 1 = odd number 3 ( n - 1 ) = 4 n - 11 3 n - 3 = 4 n - 11 Subtract 3 n to both sides 3 n - 3 - 3 n = 4 n - 11 - 3 n - 3 = n - 11 Add 11 to both sides - 3 + 11 = n - 11 + 11 8 = n n = 8 = even number n - 1 = 7 = odd number

*January 26, 2015*

**Maths**

Steve, I am from Sarajevo, Bosnia and Herzegovina. English is foreign language for me. Numerator is typing mistake, so what?

*January 26, 2015*

**Maths**

n = numerator d = denominator n = d - 2 ( n - 3 ) / ( d - 3 ) = 3 / 4 ( d - 2 - 3 ) / ( d - 3 ) = 3 / 4 ( d - 5 ) / ( d - 3 ) = 3 / 4 Multiply both sides by 4 4 ( d - 5 ) / ( d - 3 ) = ( 3 / 4 ) *4 4 ( d - 5 ) / ( d - 3 ) = 3 Multiply both sides by ( d - 3 ) 4 ( d - 5 ) ( d - ...

*January 26, 2015*

**Algebra I**

A = 4 B A + B = 160 _____________ A + B = 160 4 B + B = 160 5 B = 160 Divide both sides by 5 B = 160 / 5 = 32 min A = 4 B = 4 * 32 = 128 min

*January 26, 2015*

**algebra**

( 5 x ^ 2 - 7 x + 23 ) + 2 x ^ 2 + 9 x -72 = 5 x ^ 2 + 2 x ^ 2 - 7 x + 9 x + 23 - 72 = 7 x ^ 2 + 2 x - 49

*January 23, 2015*

**math**

- 0.15 ( x - 13 ) ^ 2 + 7.6 = 7 Subtract 7.6 to both sides - 0.15 ( x - 13 ) ^ 2 + 7.6 - 7.6 = 7 - 7.6 - 0.15 ( x - 13 ) ^ 2 = - 0.6 Divide both sides by - 0.15 ( x - 13 ) ^ 2 = - 0.6 / - 0.15 ( x - 13 ) ^ 2 = 4 Take square root to both sides x - 13 = + OR - 2 Add 13 to both ...

*January 23, 2015*

**math**

( - 5 pi / 12 ) rad = - 75 ° cos ( - x ) = cos x cos ( - 5 pi / 12 ) rad = cos ( 75 ° ) 75 ° = 45 ° + 30 ° cos ( A + B ) = cos ( A ) * cos ( B ) - sin ( A ) * Sin ( B ) cos ( 75 ° ) = cos ( 45 ° + 30 ° ) = cos ( 45° ) * cos ( 30 ° ) - ...

*January 22, 2015*

**math**

Remark : a1 = 2 n a2 = 2 ( n + 1 ) a3 = 2 ( n + 2 ) a4 = 2 ( n + 3 ) n is an integer.

*January 22, 2015*

**math**

The even integers are: a1 = 2 n a2 = 2 ( n + 1 ) a3 = 2 ( n + 2 ) a4 = 2 ( n + 3 ) a2 ^ 2 = a1 * a4 [ 2 ( n + 1 ) ] ^ 2 = 2 n * 2 ( n + 3 ) 4 ( n + 1 ) ^ 2 = 4 n * ( n + 3 ) Divide both sides by 4 ( n + 1 ) ^ 2 = n * ( n + 3 ) n ^ 2 + 2 * n * 1 + 1 ^ 2 = n * n + n * 3 n ^ 2 + ...

*January 22, 2015*

**Mathematics**

V = Velocity L = Length t = Time LA = Distance between meeting point and town A LB = Distance between meeting point and town B L = LA + LB = 120 km LA + LB = 120 Subtract LA to both sides LA + LB - LA = 120 - LA LB = 120 - LA VA = Velocity of a car which travelling town A for ...

*January 18, 2015*

**trigometry**

tan theta + cot theta = tan theta + 1 / tan theta = tan theta * tan theta / tan theta + 1 / tan theta = tan ^ 2 theta / tan theta + 1 / tan theta = ( tan ^ 2 theta + 1 ) / tan theta = ( sin ^ 2 theta / cos ^ 2 theta + cos ^ 2 theta ) / tan theta = [ ( sin ^ 2 theta + cos ^ 2 ...

*January 14, 2015*

**algebra**

z ^ - 4 = 1 / z ^ 4 z ^ - 4 / 6 x ^ 2 = ( 1 / z ^ 4 ) / 6 x ^ 2 = 1 / z ^ 4 * 6 x ^ 2 = 1 / [ 6 ( z ^ 4 * x ^ 2 ) = 1 / [ 6 ( z ^ 2 * x ) ^ 2 ]

*January 14, 2015*

**maths**

7 n + 13 = 5 n + 20 Subtract 5 n to both sides 7 n + 13 - 5 n = 5 n + 20 - 5 n 2 n + 13 = 20 Subtract 13 to both sides 2 n + 13 - 13 = 20 - 13 2 n = 7 Divide both sides by 2 n = 7 / 2

*January 12, 2015*

**alegbra 1**

3 x ^ 2 - 4 x + 1 = ( x - 1 ) ( 3 x - 1 ) 3 x ^ 2 - 3 = 3 ( x ^ 2 - 1 ) = 3 ( x + 1 ) ( x - 1 ) ( 3 x ^ 2 - 4 x + 1 ) / ( 3 x ^ 2 - 3 ) = ( x - 1 ) ( 3 x - 1 ) / [ 3 ( x + 1 ) ( x - 1 ) ] = ( 3 x - 1 ) / [ 3 ( x + 1 ) ] = 1 - 4 / [ ( 3 ( x + 1 ) ] Domain : x + 1 # 0 x # - 1 ...

*January 11, 2015*

**math**

1 cm = 1 / 100 m 100,000 x 1 cm = 1000 x 1 / 100 = 1,000 m 1,000 m = 1 km 1 cm on scale = 1 km 7 x 4 cm on scale = 7 km x 4 km = 28 km ^ 2

*January 10, 2015*

**Precal**

H = Height of the lighthouse = 200 ft L = Distance between the lighthouse and a ship theta = The angle of elevation = 21 ° tan theta = H / L tan 21 ° = 200 / L Multiply both sides b L L tan 21 ° = 200 Divide both sides by tan 21 ° L = 200 / tan 21 ° L = 200...

*January 6, 2015*

**college pre-calculus**

Correction : Your equation becomes : ( x + 1) [ x - ( 1 + i ) ] [ x - ( 1 - i ) ] ( x + 1) [ x - ( 1 + i ) ] [ x - ( 1 - i ) ] = ( x + 1 ) ( x ^ 2 - 2 x + 2 ) = x ^ 3 - x ^ 2 + 2 Answer D

*January 6, 2015*

**college pre-calculus**

1) x ^ 3 + a x ^ 2 + b x + c = ( x - x1 ) ( x - x2 ) ( x - x3 ) 2) For an equation with real coefficients, imaginary roots ( if any ) occur in conjugate pairs, i.e. f ( x ) = 0 a polynomial equation with real coefficients an n + i * m an imaginary root of it , then n - i * m ...

*January 6, 2015*

**Math**

2 x / ( x - 1 ) - 9 x / ( x - 2 ) = [ 2 x ( x - 2 ) - 9 x ( x - 1 ) ] / [ ( x - 1 ) ( x - 2 ) ] = [ 2 x * x + 2 x * ( - 2 ) - 9 x * x - 9 x * ( - 1 ) ] / ( x ^ 2 - 3 x + 2 ) = ( 2 x ^ 2 - 4 x - 9 x ^ 2 + 9 x ) / ( x ^ 2 - 3 x + 2 ) = ( - 7 x ^ 2 + 5 x ) / ( x ^ 2 - 3 x + 2...

*January 6, 2015*

**Math**

Your answer is correct.

*January 6, 2015*

**Algebra**

Draw a Cartesian coordinate system. Now : 2 x - y = 4 for x = 0 2 x - y = 4 2 * 0 - y = 4 - y = 4 Multiply both sides by - 1 y = - 4 This is first point ( x = 0 , y = 4 ) for y = 0 2 x - y = 4 2 x - 0 = 4 2 x = 4 Divide both sides by 2 x = 2 This is second point ( x = 2 , y = ...

*January 2, 2015*

**math**

a = first number b = second number Conditions: a + b = 39 2 a + 3 b = 101 ________________ a + b = 39 Subtract b to both sides a + b - b = 39 - b a = 39 - b 2 a = 2 ( 39 - b ) 2 a = 78 - 2 b 2 a + 3 b = 101 78 - 2 b + 3 b = 101 78 + b = 101 Subtract 78 to both sides 78 + b - ...

*January 2, 2015*

**Math**

P = the perimeter = 80 m A = the area W = the width L = the length P = 2 W + 2 L = 2 ( W + L ) 80 = 2 ( W + L ) Divide both sides by 2 40 = W + L Subtract L to both sides 40 - L = W + L - L 40 - L = W W = 40 - L A = W * L A = ( 40 - L ) * L A = 40 L - L ^ 2 A = - L ^ 2 + 40 L ...

*January 2, 2015*

**algebra 1**

5 x - 12 y = - 3 Miltiply both sides by - 2 - 10 x + 24 y = 6 - 10 x + 24 y = 6 + 10 x - 4 y = - 25 __________________ 0 + 20 y = - 19 20 y = - 19 Multiply both sides by 20 y = - 19 / 20 10 x - 24 y = - 6 10 x - 24 * ( - 19 ) / 20 = - 6 10 x - ( 4 * 6 ) * ( - 19 ) / ( 4 * 5...

*December 18, 2014*

**Algebra (Please help!)**

- 1 / 4 / ( 3 / 2 ) = - 1 * 2 / ( 4 * 3 ) = - 2 / 12 = - 2 / ( 2 * 6 ) = - 1 / 6

*December 13, 2014*

**please help (algebra)**

9 / 2 = 18 / 4 3 / 4 - 9 / 2 = 3 / 4 - 18 / 4 = - 15 / 4

*December 10, 2014*

**Math**

3. Becouse : | - x | = x - ( - ( - x ) ) = - x | - x | = - ( - ( - x ) ) mean: x = - x That is true only for x = 0

*December 10, 2014*

**math**

W = L - 4 P = 2 W + 2 L P = 2 ( W + L ) P = 2 ( L - 4 + L ) P = 2 ( 2 L - 4 ) P = 2 * 2 L - 2 * 4 P = 4 L - 8 56 = 4 L - 8 Add 8 to both sides 56 + 8 = 4 L - 8 + 8 64 = 4 L Divide both sides by 4 64 / 4 = 4 L / 4 16 = L L = 16 m W = L - 4 = 16 - 4 = 12 m Proof: P = 2 ( W + L...

*December 9, 2014*

**algebra**

You can write: 4 y - x = - 3 like: - x + 4 y = - 3 Now: - x + 4 y = - 3 + 2 x - 4 y = 14 _________________ - x + 2 x + 4 y - 4 y = - 3 + 14 x + 0 = 11 x = 11 4 y - x = - 3 4 y - 11 = - 3 Add 11 to both sides 4 y - 11 + 11 = - 3 + 11 4 y = 8 Divide both sides by 4 4 y / 4 = 8...

*December 9, 2014*

**Algebra**

If the room have rectangle form then : L = W + 23 P = 2 W + 2 L P = 2 ( W + L ) P = 2 ( W + W + 23 ) P = 2 ( 2 W + 23 ) P = 4 W + 46 290 = 4 W + 46 Subtract 46 to both sides 290 - 46 = 4 W + 46 - 46 244 = 4 W Divide both sides by 4 244 / 4 = 4 W / 4 61 = W W = 61 ft L = W + 23...

*December 9, 2014*

**Calculus**

The solutions of quadratic equation t ^ 2 + 2 t - 1 = 0 are : t = sqroot ( 2 ) - 1 and t = - 1 - sqroot ( 2 ) = - [ 1 +sqroot ( 2 ) ] = - 2.41421 Substitution sin ( x ) = t OR t = sin ( x ) give : sin ( x ) = sqroot ( 2 ) - 1 and sin ( x ) = - 1 - sqroot ( 2 ) = - [ 1 +sqroot...

*December 9, 2014*

**Calculus**

arc sin ( x ) is inverse sine function of x arc sin ( x ) = sin ^ - 1 ( x )

*December 9, 2014*

**Calculus**

sin ^ 2 ( x ) + cos ^ 2 ( x ) = 1 => cos ^ 2 ( x ) = 1 - sin ^ 2 ( x ) y = 2 sin ( x ) - [ 1 - sin ^ 2 ( x ) ] y = 2 sin ( x ) - 1 + sin ^ 2 x y = sin ^ 2 x + 2 sin ( x ) - 1 Substitution sin ( x ) = t y = t ^ 2 + 2 t - 1 x - intercept is a point on the graph where y is ...

*December 9, 2014*

**Algebra**

The vertex of a quadratic equation y = a x ^ 2 + b x + c is either a maximum or a minimum of the function. x = - b / 2 a gives the x - value (or the value of the function) at its vertex. y = f ( - b / 2 a ) gives the y - value (or the value of the function) at its vertex. If ...

*December 2, 2014*

**Calculus**

- 1 / 100 = const. 4 ( pi ) ^ 2 - 9 = const. sin ^ 2 x + cos ^ 2 x = 1 = const. csc x tan x cosx = ( 1 / sin x ) * ( sin x / cos x ) * cos x = 1 = const. The derivative of a constant is zero. Answer : E. All do

*December 1, 2014*

**math**

1 = 6 / 6 3 = 3 * 6 / 6 = 18 / 6 3 5 / 6 = 18 / 6 + 5 / 6 = 23 / 6

*November 24, 2014*

**calculus**

Sorry. v = ds / dt

*November 24, 2014*

**calculus**

a = ds / dt a = ( 1 / 2 ) * [ 1 / sqrt ( 6 t + 3 ) ] * 6 a = 3 / sqrt ( 6 t + 3 ) t = 1 a = 3 / sqrt ( 6 * 1 + 3 ) a = 3 / sqrt ( 6 + 3 ) a = 3 / sqrt ( 9 ) a = 3 / 3 a = 1 m / s ^ 2 Answer a.

*November 24, 2014*

**Algebra 2**

x ^ 2 + 4 y ^ 2 = 16 - x ^ 2 + y ^ 2 = 4 ______________________ 3 y ^ 2 = 12 Divide both sides by 3 y ^ 2 = 12 / 3 = 4 y = + OR - 2 For y = 2 x ^ 2 + 4 y ^ 2 = 16 x ^ 2 + 4 * 2 ^ 2 = 16 x ^ 2 + 4 * 4 = 16 x ^ 2 + 16 = 16 Subtract 16 to both sides x ^ 2 = 0 x = 0 For y = - 2 x...

*November 23, 2014*

**Calculus (PLEASE HELP ASAP!)**

1 ) f" ( x ) = 1 / x ^ 3 = x ^ ( -3 ) f´ ( x ) = integral of x ^ ( -3 ) dx f´ ( x ) = x ^ ( - 3 + 1 ) / ( - 3 + 1 ) + C f´ ( x ) = x ^ ( - 2 ) / ( - 2 ) + C f´ ( x ) = 1 / x ^ 2 / ( - 2 ) + C f´ ( x ) = - 1 / ( 2 x ^ 2 ) + C f´ ( 1 ) = ...

*November 19, 2014*

**math**

1 / 2 kg = 500 g 500 g / 50 g = 10 10 * 7 = 70 nails

*November 15, 2014*

**math**

2 / 5 = 4 / 10 = 0.4 1 / 4 of 0.4 = 0.1 0.4 - 0. 1 = 0.3 = 3 / 10 = 30 / 100 = 30 % OR 1 - 1 / 4 = 3 / 4 ( 2 / 5 ) * ( 3 / 4 ) = 6 / 20 = 2 * 3 / ( 2 * 10 ) = 0.3

*November 15, 2014*

**math**

b = mass of the basket a = mass of the aple b + 12 a = 3105 Subtract 12 a to both sides b + 12 a - 12 a = 3105 - 12 a b = 3105 - 12 a b + 7 a = 1980 3105 - 12 a + 7 a = 1980 3105 - 5 a = 1980 Subtract 1980 to both sides 3105 - 5 a - 1980 = 1980 - 1980 1125 - 5 a = 0 Add 5 a to...

*November 12, 2014*

**algebra**

g = girls age b = boys age g + b = 26 Subtract b to both sides g + b - b = 26 - b g = 26 - b g - 3 = 4 ( b - 3 ) 26 - b - 3 = 4 ( b - 3 ) 23 - b = 4 b - 12 Add b to both sides 23 - b + b = 4 b + b - 12 23 = 5 b - 12 Add 12 to both sides 23 + 12 = 5 b - 12 + 12 35 = 5 b Divide ...

*November 11, 2014*

**math**

By the way : ( 1 - x ) ^ 2 = [ ( - 1 ) ( x - 1 ) ] ^ 2 = ( - 1 ) ^ 2 ( x - 1 ) ^ 2 = 1 * ( x - 1 ) ^ 2 = ( x - 1 ) ^ 2 integral from 0 to 2 - 2 x of ( 2 - 2 x - y ) dy = 2 ( 1 - x ) ^ 2 = 2 ( x - 1 ) ^ 2

*November 4, 2014*

**math**

integral of ( 2 - 2 x - y ) dy = 2 y - 2 x y - y ^ 2 / 2 for y = 0 2 y - 2 x y - y ^ 2 / 2 = 2 * 0 - 2 x * 0 - 0 ^ 2 / 2 = 0 for y = 2 - 2 x 2 ( 2 - 2 x ) - 2 x ( 2 - 2 x ) - ( 2 - 2 x ) ^ 2 / 2 = ( 2 - 2 x ) ( 2 - 2 x ) - ( 2 - 2 x ) ^ 2 / 2 = ( 2 - 2 x ) ^ 2 - ( 2 - 2 x ) ^ ...

*November 4, 2014*

**math**

Substitution rule: y ^ 4 + 1 = t 4 y ^ 3 dy = dt Divide both sides by 4 y ^ 3 dy = dt / 4 integral of y ^ 3 dy / ( y ^ 4 + 1 ) = integral of ( dt / 4 ) / t = ( 1 / 4 ) integral of dt / t = ( 1 / 4 ) ln ( t ) = ( 1 / 4 ) ln ( y ^ 4 + 1 )

*November 4, 2014*

**math**

Replace x with given number. f ( 2 ) = - 3 * 2 + 9 = - 6 + 9 = 3 f ( - 2 ) = - 3 * ( - 2 ) + 9 = 6 + 9 = 15

*October 31, 2014*

**Pre-Calc/Trig...**

( 2 x ^ 3 + x ^ 2 - 5 x + 2 ) / ( x + 2 ) = 2 x ^ 2 - 3 x + 1 2 x ^ 2 - 3 x + 1 = ( x - 1 ) ( 2 x - 1 ) So : 2 x ^ 3 + x ^ 2 - 5 x + 2 = ( x + 2 ) ( x - 1 ) ( 2 x - 1 ) x + 2 is one of fators of : 2 x ^ 3 + x ^ 2 - 5 x + 2

*October 31, 2014*

**Pre-Calc/Trig...**

( 2 x ^ 3+ x ^ 2 - 5 x + 2 ) / ( x + 2 ) = 2 x ^ 2 - 3 x + 1 In google type . calc 101 When you see list of results click on : c a l c 1 0 1 . c o m When page be open click on : long division In rectangle : Divide type : 2x^3+x^2-5x+2 In rectangle : by type : x+2 Then click ...

*October 31, 2014*

**Algebra: PLEASE HELP ME! :(**

Replace x with , b - 2 Firs coordinate is x. In this case : b - 2 Second coordinate is : y = f ( x ) = f ( b - 2 ) So : b - 2 , f( b - 2 )

*October 31, 2014*

**Math**

The dimensions of the box : 51 - 2 x and 45 - 2 x The volume of the box: ( 51 - 2 x ) * ( 45 - 2 x ) * x = 7750 51 * 45 - 2 x * 45 - 2 x * 51 - 2 x * ( - 2 x ) * x = 7750 ( 2295 - 90 x - 102 x + 4 x ^ 2 ) * x = 7750 ( 4 x ^ 2 - 192 x + 2295 ) * x = 7750 4 x ^ 3 - 192 x ^ 2 + ...

*October 30, 2014*

**algebra math**

Formula for a geometric sequence : an = a1 * r ^ ( n - 1 ) an is the nth term, a1 is the first term, r is the common ratio. In this case : a = 8 r = 1 / 2 a1 = 8 * ( 1 / 2 ) ^ ( 1 - 1 ) a1 = 8 * ( 1 / 2 ) ^ 0 a1 = 8 * 1 = 8 a2 = 8 * ( 1 / 2 ) ^ ( 2 - 1 ) a2 = 8 * ( 1 / 2 ) ^ 1...

*October 28, 2014*

**Pre-Calc/Trig**

y = - ( x - 9 ) ( x + 4 )

*October 27, 2014*

**algebra**

24 + y

*October 26, 2014*

**math**

96 m / 4 s = 24 m / s

*October 22, 2014*

**math**

In google type : quadratic equation online When you see list of results click on : w w w . w e b g r a p h i n g . c o m / q u a d r a t i c e q u a t i o n _ q u a d r a t i When page be open in rectangle type: 2465=204.8t+4.6t^2 and click option : solve it! You will see ...

*October 19, 2014*

**Math**

In a geometric sequence, consecutive terms have a common ratio. This can be expressed as: a(n) / a(n-1) = q In this case: a2 / a1 = q and a3 / a2 = q Of course q = q a2 / a1 = a3 / a2 Sequence: 2 x , 4 x - 2 , 6 x - 4 a1 = 2 x , a2 = 4 x - 2 , a3 = 6x-4 a2 / a1 = a3 / a2 ( 4 x...

*October 18, 2014*

**math**

A = 3 B C = 2 A + 10 ° C = 2 * 3 B + 10 ° C = 6 B + 10 ° A + B + C = 180 ° 3 B + B + 6 B + 10 ° = 180 ° 10 B + 10 ° = 180 ° Subtract 10 ° to both sides 10 B + 10 ° - 10 ° = 180 ° - 10 ° 10 B = 170 ° Divide both sides by ...

*October 15, 2014*

**math**

c 0 / 10 = 0 / - 10 0 = 0 0 divided by any number is 0

*October 14, 2014*

**Algebra 1**

80 km = 80,000 m 1 h = 3,600 s 80,000 / 3,600 = 4 * 20,000 / ( 4 * 900 ) = 20,000 / 900 = 200 * 100 / ( 9 * 100 ) = 200 / 9 = 22.222 m / s

*October 11, 2014*

**Math Help**

x ^ 3 - 4 x ^ 2 - 25 x + 100 = ( x ^ 3 - 4 x ^ 2 ) + ( - 25 x + 100 ) = ( x ^ 3 - 4 x ^ 2 ) - ( 25 x - 100 ) = x ^ 2 ( x - 4 ) - 25 ( x - 4 ) = ( x - 4 ) ( x ^ 2 - 25 ) = ( x - 4 ) ( x + 5 ) ( x - 5 ) ___________________________________ Remark : a ^ 2 - b ^ 2 = ( a + b ) ( a...

*October 10, 2014*

**Algebra**

Yes, becouse: 2 x ^ 2 - 12 x + 40 = 0 Divide both sides by 2 x ^ 2 - 6 x + 20 = 0 First equation is second equation multiplied by 2 and 2 * 0 = 0

*October 7, 2014*

**Math**

- 3.702 + ( - 9.78 ) = - 3.702 - 9.78 = -13.482

*October 7, 2014*

**Math**

- 3.702 + ( - 9.78 ) = - 3.702 - 9.78 = - -13.482

*October 7, 2014*

**math**

a = Number of adults c = Number of children Total numbers of spectator = 441 a + c = 441 Total proceeds = 13,797 $ a * 45 $ + c * 21 $ = 13,797 $ Now you must solve system of two equation : a + c = 441 45 a + 21 c = 13,797 Try it. The solutions are : a = 189 c = 252 Proof : a...

*October 6, 2014*

**calculus**

In google type : quadratic equation online When you see list of results click on : w w w . w e b g r a p h i n g . c o m / q u a d r a t i c e q u a t i o n _ q u a d r a t i When page be open click on : Solve by Completing the Square Then in rectangle type equation and click ...

*October 6, 2014*

**Math**

K = Kates age L = Lannys age M = Marias age N = Normans age K = L + 5 L = M - 2 M = 2 N N = 10 M = 2 N M = 2 * 10 = 20 L = M - 2 = 20 - 2 = 18 K = L + 5 = 18 + 5 = 23

*October 3, 2014*

**Algebra 1 Check**

¡Ü mean less or equal

*October 3, 2014*

**Algebra 1 Check**

c.) 4 x ^ 2 ¡Ü ( 4 x ) ^ 2 4 x ^ 2 ¡Ü 16 x ^ 2 Subtract 4 x ^ 2 to both sides 4 x ^ 2 - 4 x ^ 2 ¡Ü 16 x ^ 2 - 4 x ^ 2 0 ¡Ü 12 x ^ 2 Divide both sides by 12 0 ¡Ü x ^ 2 This is equivalent of 0 ¡Ü x 0 < x OR 0 &...

*October 3, 2014*

**Algebra 2**

A = 1 / 2 h ( c + d ) Multiply both sides by 2 2 A = h ( c + d ) Divide both sides by ( c + d ) 2 A / ( c + d ) = h h = 2 A / ( c + d )

*October 2, 2014*

**Math**

( ( x - 8 ) - ( x - 3 ) )/ ( 8 - x ) = [ ( x - 8 - x - ( - 3 ) ] / ( 8 - x ) = ( x - 8 - x + 3 / ( 8 - x ) = - 5 / ( 8 - x ) = - 5 / - ( x - 8 ) = 5 / ( x - 8 )

*October 2, 2014*

**Pre-Calculus/Trigonometry**

You're welcome.

*September 30, 2014*

**Pre-Calculus/Trigonometry**

a. Replace x with 3 f ( 3 )= 1 / ( x ^ 2 - 3 ) = 1 / ( 3 ^ 2 - 3 ) = 1 / ( 9 - 3 ) = 1 / 6 b. Replace x with 2 + h f ( 2 + h )= 1 / [ ( 2 + h ) ^ 2 - 3 ] = 1 / ( 2 ^ 2 + 2 * 2 * h + h ^ 2 - 3 ) = 1 / ( 4 + 4 h + h ^ 2 - 3 ) = 1 / ( h ^ 2 + 4 h + 1 )

*September 30, 2014*

**Math**

1 .) c. sqrt ( 4 ) + sqrt ( 9 ) = 2 + 3 = 5 2 .) b. sqrt ( 36 ) * sqrt ( 49 ) = 6 * 7 = 43 3 .) sq root of - 66 = sqrt ( - 1 ) * sqrt ( 66 ) = i * 8.124 approx. 8 i Remarq ( i ) = sqrt ( - 1 ) 4 .) sqrt ( 3 ) = 1.732 1. 7 round to the nearest tenth c. 5. ) sqrt ( 112 ) = 10....

*September 30, 2014*

**math- pre calc/trig**

d = square root ( a ^ 2 + a ^ 2 ) d = square root ( 2 a ^ 2 ) d = square root ( 2 ) * square root ( a ^ 2 ) d = square root ( 2 ) * a 7 square root ( 2 ) = square root ( 2 ) * a Divide both sides by square root ( 2 ) 7 = a a = 7

*September 30, 2014*

**Math**

Yes. All negative numbers can be either odd or even. An even number must be integrally divisible by 2. - 2 is an even number. - 2 / 2 = - 1

*September 30, 2014*

**math**

1 in = 0.0254 m 1 ft = 12 in = 12 * 0.0254 = 0.3048 1 ft = 0.3048 m 1 ft ^ 2 = ( 0.3048 ) ^ 2 m ^ 2 1 ft ^ 2 = 0,09290304 m ^ 2 75 ft ^ 2 = 75 * 0.09290304 m ^ 2 75 ft ^ 2 = 6.967728 m ^ 2 75 ft ^ 2 = approx. 7 m ^ 2

*September 25, 2014*

**Algebra (Quadratics)**

y = ( - 1 / 10 ) x ^ 2 + 3 x + 6 for x = 30 ft y = ( - 1 / 10 ) * 30 ^ 2 + 3 * 30 + 6 = ( - 1 / 10 ) * 900 + 90 + 6 = - 900 / 10 + 90 + 6 = - 90 + 90 + 6 = 6 ft 6 ft > 5 ft The ball will fly over the head of another child.

*September 25, 2014*

**Math (Quadractic function)**

a. N ( T ) = 10 T ^ 2 - 20 T + 600 T ( t ) = 3 t + 2 N ( T ( t ) ) = 10 * ( 3 t + 2 ) ^ 2 - 20 * ( 3 t + 2 ) + 600 = 10 * [ ( 3 t ) ^ 2 + 2 * 3 t * 2 + 2 ^ 2 ] - 20 * 3 t - 20 * 2 + 600 = 10 * ( 9 t ^ 2 + 12 t + 4 ) - 60 t - 40 + 600 = 90 t ^ 2 + 120 t + 40 - 60 t - 40 + 600...

*September 25, 2014*

**Pre-Calculus**

In the standard ( or general ) form the linear equation is written as: A x + B y = C In this case: A = 3 B = - 2 C = 4 Standard form

*September 24, 2014*

**Maths**

b = the number of boys g = the number of girls b / g = 4 / 7 Multiply both sides by 7 7 b / g = 4 Multiply both sides by g 7 b = 4 g Divide both sides by 4 7 b / 4 = g g = 7 b / 4 g = 12 + b 7 b / 4 = 12 + b Subtract b to both sides 7 b / 4 - b = 12 + b - b 7 b / 4 - b = 12 7 ...

*September 24, 2014*

**algebra**

a = number of adults c = number of childrens number of adults + number of childrens = 600 total a + c = 600 a * 15 $ + c * 8 $ = 7740 $ 15 a + 8 c = 7740 Now you must solve system of two equations: a + c = 600 15 a + 8 c = 7740 The solutions are : a = 420 c = 180 420 adults ...

*September 23, 2014*

**8th grade homework**

Steps: x = a number 1. Six is subtracted from a number: x - 6 2. The result is devided by four: ( x - 6 ) / 4 3. This result is added to 10 to give 30: ( x - 6 ) / 4 + 10 = 30 So : ( x - 6 ) / 4 + 10 = 30 Subtact 10 to both sides ( x - 6 ) / 4 + 10 - 10 = 30 - 10 ( x - 6 ) / 4...

*September 14, 2014*

**Algebra**

v1 = an average velocity travel to island = 18 knopts v2 = an average velocity on the return = 10 knots t1 = time of travel to island t2 = time on the return L = Distance betwen harbor and island t = t1 + t2 = total time of trip = 14 h v1 = L / t1 18 = L / t1 L / t1 = 18 v2 = ...

*September 14, 2014*

**math**

Enclosure is divide into two equal parts. Thats why you hawe width 3 times. Two times of end of fence and one time in midle. You hawe length 2 times both times of end of fence. So: 3 W + 2 L = 500 3 W = 500 - 2 L = 2 ( 250 - L ) 3 W = 2 ( 250 - L ) Divide both sides by 3 W...

*September 14, 2014*

**Maths**

1 h = 60 min 1 min = 1 / 60 1 min = 11 / 60 h 1 min = 0,18333333 h

*September 14, 2014*

**Pre-Calculus**

2 x ^ 3 - 3 x ^ 2 - 2 x + 3 = 0 ( 2 x ^ 3 - 2 x ) - 3 x ^ 2 + 3 = 0 _________________________________ Remark : - 3 x ^ 2 + 3 = - ( 3 x ^ 2 - 3 ) _________________________________ ( 2 x ^ 3 - 2 x ) - ( 3 x ^ 2 - 3 ) = 0 2 x ( x ^ 2 - 1 ) - 3 ( x ^ 2 - 1 ) = 0 ( x ^ 2 - 1 ) ( 2 ...

*September 14, 2014*

**Pre-Calculus**

x ^ 4 + a x ^ 3 + b x ^ 2 + c x + d = ( x - x1 ) ( x - x2 ) ( x - x3 ) ( x - x4 ) = ( x - 1 ) [ x - ( - 1 ) ] [ x - 2 ) ] ( x - 1 / 2 ) ( x - 1 ) ( x + 1 ) ( x - 2 ) ( x - 1 / 2 ) = x ^ 4 - 5 x ^ 3 / 2 + 5 x / 2 - 1

*September 14, 2014*

**algebra 2**

9 | 9 - 8 x | = 2 x + 3 Divide both sides by 9 | 9 - 8 x | = 2 x / 9 + 3 / 9 | 9 - 8 x | = 2 x / 9 + 1 / 3 + OR - ( 9 - 8 x ) = 2 x / 9 + 1 / 3 1. + ( 9 - 8 x ) = 2 x / 9 + 1 / 3 9 - 8 x = 2 x / 9 + 1 / 3 Subtract 9 to both sides 9 - 8 x - 9 = 2 x / 9 + 1 / 3 - 9 - 8 x = 2 x...

*September 5, 2014*

**Algebra**

- 2 | 3 y + 7 | + 9 = 5 Subtract 9 to both sides - 2 | 3 y + 7 | + 9 - 9 = 5 - 9 - 2 | 3 y + 7 | = - 4 Divide both sides by - 2 | 3 y + 7 | = - 4 / - 2 | 3 y + 7 | = 2 + OR - ( 3 y + 7 ) = 2 3 y + 7 = 2 Subtract 7 to both sides 3 y + 7 - 7 = 2 - 7 3 y = - 5 Divide both sides ...

*August 31, 2014*

**math**

Factor pair : ( - 2 , - 9 ) So : x ^ 2 - 11 x + 18 = ( x - 2 ) ( x - 9 ) = 0

*August 30, 2014*

**Algebra II**

a = the first side b = the second side c = the third side P = the perimeter a = 2 b - 5 c = a + 2 = 2 b - 5 + 2 = 2 b - 3 P = a + b + c = 47 a + b + c = 47 2 b - 5 + b + 2 b - 3 = 47 5 b - 8 = 47 Add 8 to both sides 5 b - 8 + 8 = 47 + 8 5 b = 55 Divide both sides by 5 b = 11 ...

*August 30, 2014*

**math**

A Prime Numbers can be divided evenly only by 1 or itself. 1 , 3 , 5 , 7 , 11 , 13 ,17 ... 5 is prime number

*August 27, 2014*

**Math**

21 / 25 = 4 * 21 / ( 4 * 25 ) = 84 / 100 = 84 %

*August 27, 2014*

**math**

68 + 7 = 75 93 + ( 68 + 7 ) = 93 + 75 = 168

*August 27, 2014*

**Math**

Yes

*August 27, 2014*

**Math**

a ^ m * a ^ n = a ^ ( m + n ) y ^ ( - 9 ) * y ^ 3 = y ^ ( - 9 + 3 ) = y ^ ( - 6 ) = 1 / y ^ 6

*August 27, 2014*

**Math**

72 = 2 Ka Divide both sides by 2

*August 26, 2014*